2015
DOI: 10.1115/1.4030181
|View full text |Cite
|
Sign up to set email alerts
|

Connections Between the Design Tool, Design Attributes, and User Preferences in Early Stage Design

Abstract: Gathering user feedback on provisional design concepts early in the design process has the potential to reduce time-to-market and create more satisfying products. Among the parameters that shape user response to a product, this paper investigates how design experts use sketches, physical prototypes, and computer-aided design (CAD) to generate and represent ideas, as well as how these tools are linked to design attributes and multiple measures of design quality. Eighteen expert designers individually addressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 45 publications
1
42
0
Order By: Relevance
“…In contrast to design experts, who use prototypes early in a project to engage with stakeholders, novice designers primarily reported using prototypes with stakeholders later in the design process to share their progress and gather feedback. This echoes studies that have found that novice designers spend less time scoping a problem and do not seek the same depth and breadth of information prior to developing design solutions (Atman et al, 2007; Häggman et al, 2015; Mohedas, Daly, & Sienko, 2014b; Viswanathan, Atilola, Goodman, et al, 2014; Yang & Epstein, 2005). This lack of engagement with stakeholders early in the design process represents a missed opportunity and has the potential to negatively impact design outcomes.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In contrast to design experts, who use prototypes early in a project to engage with stakeholders, novice designers primarily reported using prototypes with stakeholders later in the design process to share their progress and gather feedback. This echoes studies that have found that novice designers spend less time scoping a problem and do not seek the same depth and breadth of information prior to developing design solutions (Atman et al, 2007; Häggman et al, 2015; Mohedas, Daly, & Sienko, 2014b; Viswanathan, Atilola, Goodman, et al, 2014; Yang & Epstein, 2005). This lack of engagement with stakeholders early in the design process represents a missed opportunity and has the potential to negatively impact design outcomes.…”
Section: Discussionsupporting
confidence: 59%
“…Camburn et al, 2015; B. A. Camburn et al, 2013; Häggman, Tsai, Elsen, Honda, & Yang, 2015; Yang & Epstein, 2005). Design experts leverage their accumulated knowledge and experience and select the most appropriate approaches to prototyping to answer specific design questions (Houde & Hill, 1997), and expert designers rely heavily on prototypes to quickly test an idea or generate new ones.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Fully-synchronous CAD software provides an appealing instrument with which to explore these factors. An example future study of interest would investigate the creativity of the product enabled by fully-synchronous collaborative design teams when compared to results already discovered for creativity with traditional CAD use and other virtual tools (Chulvi et al, 2017;Häggman et al, 2015;Robertson and Radcliffe, 2009). Another might be a study of team composition, specific to the CAD context and compared to previous findings on collaborative design (McComb et al, 2016).…”
Section: Future Workmentioning
confidence: 97%
“…More research is required to support design teams seeking specific outcomes. Many more empirical studies have been performed of traditional design method outcomes, especially attempts to quantify innovation / creativity driven by design activities , (Sarkar and Chakrabarti, 2011), (Oman et al, 2013), (Häggman et al, 2015), (Yilmaz et al, 2016). The most famous metrics may be Shah's "variety", "novelty", "quantity", and "quality" .…”
Section: Introductionmentioning
confidence: 99%